Strengthening Makharij al-Huruf Competence through Digitalization: An Academic Review of Quranic Tahsin Science - Nelvawita, Nelvawita; S, Mochammad Novendri (Jurnal Ushuluddin, 2024)
The activity of reading the Quran is an essential lesson that every Muslim must understand, as it serves as a guide in life and holds significant value in worship. However, the process of learning to read the Quran is often neglected today due to technological advancements and the preference for Latin script readings, which are considered less important. This study aims to present a media development product for learning the makharijul letters of the Quran using the Tahsin Digital Augmented Reality Android application platform. The research follows the Research and Development (R&D) methodology based on the Borg and Gall model. After several stages of development, the study found that the media created for learning makharijul letters through this Augmented Reality digital Tahsin application is accessible on the Google Play Store for Android devices. According to feedback from experts in Tahsin and technology, the application is highly valid and effective in supporting the learning of makharijul letters. This is due to the unique delivery of each letter through Augmented Reality technology, complemented by animations and audio samples provided by scientifically verified experts. The Tahsin Digital Augmented Reality application is suitable for users ranging from basic education to higher education levels.